PENGEOLAAN SAMPAH DI KECAMATAN PASAR MUARA BUNGO KABUPATEN BUNGO - chadijah nengsih nengsih; ernawati .; ratna wilis (JURUSAN GEOGRAFI FIS UNP, 2018)
Abstract This research was conducted in Kecamatan Pasar Muara Bungo Kabupaten Muara Bungo study aims to (1) To know the waste management in Muara Bungo Market District (2) To know what factors affect the waste management in Kecamatan Pasar Muara Bungo. The method used in this research is descriptive method. Technique of collecting data obtained from result of documentation and result of spreading of questionnaire with janitor. Data analysis technique used is by using technique of Proportionate Random Sampling. The results show that (1) waste management in Bungo Regency has been running well but there are some plans that have not been achieved yet. Nevertheless, waste management in Kecamatan Pasar Muara Bungo has not been running smoothly because in general, the cleaners in Kecamatan Pasar Muara Bungo only do the job without planning, arranging and supervising their work in managing waste, the availability of unmet garbage collector. (2) Factors affecting waste management in Kecamatan Pasar Muara Bungo are the existence of government planning that has not been done yet, lack of available garbage collectors, narrow garbage collection route coverage, lack of awareness of the local people about the importance of good waste management, Lack of awareness from officers in waste management itself such as supervision, arrangement, and planning in work. Keywords: Management, Waste, Facility